2013
DOI: 10.1155/2013/471659
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract ofPaeonia lactifloraand Paeoniflorin as Aggregation Reducers Targeting Chaperones in Cell Models of Spinocerebellar Ataxia 3

Abstract: Spinocerebellar ataxia (SCA) types 1, 2, 3, 6, 7, and 17 as well as Huntington's disease are a group of neurodegenerative disorders caused by expanded CAG repeats encoding a long polyglutamine (polyQ) tract in the respective proteins. Evidence has shown that the accumulation of intranuclear and cytoplasmic misfolded polyQ proteins leads to apoptosis and cell death. Thus suppression of aggregate formation is expected to inhibit a wide range of downstream pathogenic events in polyQ diseases. In this study, we es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Most recently, studies have focused on the role of PF in protein aggregation diseases such as Parkinson's disease and Alzheimer's disease and in the degradation of aggregation-prone proteins. For example, Chang et al [ 14 ] found that PF significantly prohibited the aggregation of polyQ proteins and upregulated HSF1 and HSP70 chaperones in both 293 ATXN3/Q75-GFP cells and SH-SY5Y ATXN3/Q75-GFP cells. Others have shown that PF protects PC12 cells against MPP+ induced injury by upregulating the autophagic pathway [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, studies have focused on the role of PF in protein aggregation diseases such as Parkinson's disease and Alzheimer's disease and in the degradation of aggregation-prone proteins. For example, Chang et al [ 14 ] found that PF significantly prohibited the aggregation of polyQ proteins and upregulated HSF1 and HSP70 chaperones in both 293 ATXN3/Q75-GFP cells and SH-SY5Y ATXN3/Q75-GFP cells. Others have shown that PF protects PC12 cells against MPP+ induced injury by upregulating the autophagic pathway [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds were also studied: the aqueous extract of Paeonia lactiflora and its constituents and the aqueous extract of Glycyrrhiza inflata reduced ataxin‐3 aggregation in cellular models (Chang et al . ; Chen et al . ).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…A pcDNA5/FRT/TO-derived fluorescent reporter plasmid with mCherry, ZsYellow1, and AmCyan1 reporters driven by HSF1 (to enhance chaperone expression), heat shock cognate protein (HSPA8, to drive constitutively expressed HSP70), and heat-inducible HSP70 chaperone (HSPA1A, to drive heat-inducible HSP70) promoter fragments, respectively, was cloned as described. 29 The resulting plasmid was used to generate triple fluorescent reporter cells and maintained in accordance with the supplier’s instructions (Invitrogen). GGA, indole, or NC001-8 (100 nM~100 μM) was added to the medium for 24 hours.…”
Section: Methodsmentioning
confidence: 99%